2023
DOI: 10.1021/acs.jpclett.3c00722
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dopant–Host Energy-Level Alignment: Toward a Better Understanding of the Photoluminescence Behaviors of Doped Phosphors

Abstract: Luminescent materials, also known as phosphors, have been widely used for applications such as emissive displays, fluorescent lamps, light-emitting diodes, and X-ray scintillation detectors. The energy-level diagram of a phosphor is extremely important for understanding its photoluminescence behavior. Here, we demonstrate through a combined density functional theory and experimental study that excited-state energy-level alignment accounts for the photoluminescence behaviors much better than ground-state energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…To sum up, the arrangement of metal halide octahedra has a significant impact on the intrinsic defects of the host, and further, in aliovalent doping, the dopant center will combine with the intrinsic defects of the host to affect the properties of the lowest excited state of the original dopant center. Therefore, even with similar octahedral spatial configurations, different associations of dopant centers and intrinsic defects of the host will lead to different luminescence phenomena, such as Sb:Rb 4 CdCl 6 , Rb 3 InCl 6 , and Cs 2 (Sn, Zr, Hf)Cl 6 . ,, Besides, Sb 3+ -doped Cd-based halides exhibit defect tolerance, and even defect-assisted luminescence in the CsCdCl 3 , (NH 4 ) 2 SnCl 6 and Cs 2 (Sn,Zr,Hf)Cl 6 systems. ,,, Furthermore, the “positive charge” aliovalent substitution of the metal ions in the six-coordinated face-shared substrates tends to the formation of metal-ion vacancies in the same dimer. These vacancies have a substantial influence on the lowest excited state properties of the doping center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, the arrangement of metal halide octahedra has a significant impact on the intrinsic defects of the host, and further, in aliovalent doping, the dopant center will combine with the intrinsic defects of the host to affect the properties of the lowest excited state of the original dopant center. Therefore, even with similar octahedral spatial configurations, different associations of dopant centers and intrinsic defects of the host will lead to different luminescence phenomena, such as Sb:Rb 4 CdCl 6 , Rb 3 InCl 6 , and Cs 2 (Sn, Zr, Hf)Cl 6 . ,, Besides, Sb 3+ -doped Cd-based halides exhibit defect tolerance, and even defect-assisted luminescence in the CsCdCl 3 , (NH 4 ) 2 SnCl 6 and Cs 2 (Sn,Zr,Hf)Cl 6 systems. ,,, Furthermore, the “positive charge” aliovalent substitution of the metal ions in the six-coordinated face-shared substrates tends to the formation of metal-ion vacancies in the same dimer. These vacancies have a substantial influence on the lowest excited state properties of the doping center.…”
Section: Resultsmentioning
confidence: 99%
“…3,13,14 Besides, Sb 3+ -doped Cd-based halides exhibit defect tolerance, 50 and even defect-assisted luminescence in the CsCdCl 3 , (NH 4 ) 2 SnCl 6 51 and Cs 2 (Sn,Zr,Hf)Cl 6 systems. 38,43,44,52 Furthermore, the "positive charge" aliovalent substitution of the metal ions in the six-coordinated face-shared substrates tends to the formation of metal-ion vacancies in the same dimer. These vacancies have a substantial influence on the lowest excited state properties of the doping center.…”
Section: • and [Sb Cd2mentioning
confidence: 99%
“…The calculated band structures of 1 - wh , 1 - bu , and 1 - gn are almost the same. These results indicated that all of these compounds exhibit a type-II band alignment between the [Cu 4 I 4 ] and conjugated organic matrices in the ground state (i.e., the lowest unoccupied molecular orbital of the organic cation is lower than the unoccupied Cu 4s orbitals while the highest occupied molecular orbital of the organic cation is lower than the occupied Cu 3d orbitals). The qualitative molecular orbital diagram is used to explore the band alignment of the Cu 4 I 4 L 4 unit in Figure b. When the Cu 4 cluster forms, the 4s orbitals of Cu 4 exhibit a low-lying singlet bonding state (a 1 ) in the valence band.…”
mentioning
confidence: 99%